1993
DOI: 10.1002/cne.903270406
|View full text |Cite
|
Sign up to set email alerts
|

Localization of cannabinoid receptor mRNA in rat brain

Abstract: Cannabinoid receptor mRNA was localized in adult rat brain by 35S-tailed oligonucleotide probes and in situ hybridization histochemistry. Labelling is described as uniform or non-uniform depending on the relative intensities of individual cells expressing cannabinoid receptor mRNA within a given region or nucleus. Uniform labelling was found in the hypothalamus, thalamus, basal ganglia, cerebellum and brainstem. Non-uniform labelling that resulted from the presence of cells displaying two easily distinguishabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

43
442
2
20

Year Published

1996
1996
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 585 publications
(514 citation statements)
references
References 42 publications
43
442
2
20
Order By: Relevance
“…6F). CB 1 -immunoreactivity in the molecular layer is largely associated with the parallel fibers of granule cells, consistent with CB 1 mRNA expression in granule-cell somata (Matsuda et al, 1993). Fig.…”
Section: Cerebral Cortex and Cerebellar Cortexsupporting
confidence: 75%
“…6F). CB 1 -immunoreactivity in the molecular layer is largely associated with the parallel fibers of granule cells, consistent with CB 1 mRNA expression in granule-cell somata (Matsuda et al, 1993). Fig.…”
Section: Cerebral Cortex and Cerebellar Cortexsupporting
confidence: 75%
“…In situ hybridization studies indicate low to moderate CB1 expression levels in pyramidal cells, [25][26][27]29,46 but despite the extensive search and use of novel antisera recognizing both proposed splice variants of CB1, 39 neither the cell bodies and dendrites, nor the axon terminals of pyramidal cells were found to express this receptor. In contrast, this complete lack of immunostaining in pyramidal cells does not exclude the possibility that our antibodies could recognize only those cells, which express high levels of CB1.…”
Section: Similar Distribution Pattern Of Cb1 Cannabinoid Receptors Inmentioning
confidence: 99%
“…4,31,38 In contrast, CB1 mRNA was only found in these principal cells at low levels, slightly above the background, or low to moderate levels in the aged human hippocampus. [25][26][27]29,46 In the present study, we aimed to identify the precise cellular expression pattern and the subcellular localization (final plasma membrane destination) of CB1 receptors, and to investigate cannabinoid effects on GABA release in the human hippocampus. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25 High levels of mRNA of CB1 gene were found by in situ hybridization in the rat limbic system, linking CB1 activity with memory and emotions. 26 THC inhibits synaptic release of dopamine, 5-HT, GABA and noradrenaline. 27 It has been suggested that the THC inhibitory role on dopamine and serotonin systems may be the origin of the lack of motivation and depression symptoms in marihuana consumers.…”
Section: Introductionmentioning
confidence: 99%